B-doped 3C-SiC nanowires with a finned microstructure for efficient visible light-driven photocatalytic hydrogen production1. Issue 19 (21st May 2015) - Yang, Tao; Chang, Xiwang; Chen, Junhong; Chou, Kuo-Chih; Hou, Xinmei
<x xml:space="preserve">Abstract</x> B-doped 3C-SiC nanowires with a finned microstructure have been synthesized. Due to the smaller band gap, the finned microstructure, and the single crystalline nature, the B-doped 3C-SiC nanowires demonstrate efficient activity as high as 108.4 μmol h−1 g−1 for H2 production.